2002
DOI: 10.1016/s0925-4773(02)00089-8
|View full text |Cite
|
Sign up to set email alerts
|

Arginase expression in mouse embryonic development

Abstract: We are using the model of the developing mouse embryo to elucidate the pattern of arginase expression in mammalian cells in normal animals and in arginase I (AI) deficiency during development by digoxigenin-labeled RNA in situ hybridization. Our goal is to understand the regulation of these isozymes, with the expectation that this knowledge will help patients suffering from AI deficiency. We found that AI mRNA was widely and strongly expressed in the normal developing mouse embryo; in contrast, a relatively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…The mucous gland epithelium was stained reddishpurple, whereas the serous salivary gland was stained blue-purple only by hematoxylin ( Figure 3A2). H&E staining was used for confirmation of leukocytes and other tissues, as demonstrated in our previous study (Yu et al 2002). …”
Section: Histochemistry and Cytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The mucous gland epithelium was stained reddishpurple, whereas the serous salivary gland was stained blue-purple only by hematoxylin ( Figure 3A2). H&E staining was used for confirmation of leukocytes and other tissues, as demonstrated in our previous study (Yu et al 2002). …”
Section: Histochemistry and Cytochemistrymentioning
confidence: 99%
“…We recently reported the patterns of arginase isozyme expression in mouse brain and embryo (Yu et al 2001(Yu et al ,2002. We began with the idea from prior work in humans and rodents that AI was responsible primarily for urea synthesis and that AII was likely to be primarily responsible for the biosynthesis of ornithine, subsequently leading to the production of other biologically relevant molecules such as polyamine and glutamate or proline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These arginase isoforms differ in terms of tissue distribution, subcellular localization, immunologic cross-reactivity, and physiologic functions. During early developmental stages, Arg 1 is expressed predominantly in the peripheral nervous system, the digestive system and in tissue leukocytes, whereas Arg 2 is found only in the intestines (16). Cytosolic Arg 1 is involved in ammonia degradation in the urea cycle, and its absence in deficient patients leads to hyperammonemia.…”
mentioning
confidence: 99%
“…There is no arginase II in rodent islets, whereas exocrine tissue contains weak arginase I and no arginase II (37). Arginase I is widely expressed in mouse tissues, especially in the upper gastrointestinal tract, and is seen also during embryonic development in pancreas and is much more pronounced in glandular cells in early development (39). Studies with Western blots demonstrated that rat islets and RINm5F cells express mainly arginase I (37).…”
Section: Discussionmentioning
confidence: 99%